Partisipasi Masyarakat Nagari Sikabu Kecamatan LubukAlung dalam Pembebasan Lahan Pembangunan Stadion Utama Sumatera Barat - Fathur Rizqi (Jurnal Sosiologi Andalas, 2019)
Abstract: West Sumatra, which in the Minangkabau tradition, land is a high heirloom property that must beprotected and cannot be sold or misused. This study aims to describe the participation of local communities inland acquisition for the construction of the West Sumatra Main Stadium. The theory used in this research issocial capital theory from Robert M.Z Lawang which explains trust, social networks, and norms in buildingcommunity participation. This research uses qualitative methods and descriptive research type. Data collectionwas carried out by observation and interviews. The belief that was found was the existence of tribal ties betweenlandowners, secondly because of shared experience in solving problems, third because of the role of communityleaders, in this case the customary mamak with the title Datuak, fourth because of the certainty of compensationprices that did not harm the community or government, fifth because there is a guarantee of honesty andopenness from related parties including community leaders who will protect the rights of the Sikabu communityand do not allow additional land by parties who are not responsible for their personal interests. Networks cancreate trust between the characters involved. The norms found in the Sikabu community are the custom ofsalingka nagari and the function of the tigo sajarangan stove which can play its role well.